2016
DOI: 10.1007/s10858-016-0040-2
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free expression, purification, and membrane reconstitution for NMR studies of the nonstructural protein 4B from hepatitis C virus

Abstract: We describe the expression of the hepatitis C virus (HCV) nonstructural protein 4B (NS4B), which is an integral membrane protein, in a wheat germ cell-free system, the subsequent purification and characterization of NS4B and its insertion into proteoliposomes in amounts sufficient for multidimensional solid-state NMR spectroscopy. First spectra of the isotopically 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 53 publications
1
31
0
2
Order By: Relevance
“…As a result, the 2.5‐fold excess of mβ‐CD over the minimal amount determined, combined with PC/Chol solubilized in Triton X‐100, yielded the spectra with best resolution and signal‐to‐noise ratio (SNR), and this condition was thus set as the sample preparation standard. Finally, 2D 1 H, 15 N correlation spectra (Figure S3) confirmed that NS4B lipid reconstitution using cyclodextrin indeed yielded very similar NMR spectra as the more time‐consuming reconstitution using Bio‐Bead‐enhanced dialysis, and could thus be used as starting point for further optimizations.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…As a result, the 2.5‐fold excess of mβ‐CD over the minimal amount determined, combined with PC/Chol solubilized in Triton X‐100, yielded the spectra with best resolution and signal‐to‐noise ratio (SNR), and this condition was thus set as the sample preparation standard. Finally, 2D 1 H, 15 N correlation spectra (Figure S3) confirmed that NS4B lipid reconstitution using cyclodextrin indeed yielded very similar NMR spectra as the more time‐consuming reconstitution using Bio‐Bead‐enhanced dialysis, and could thus be used as starting point for further optimizations.…”
Section: Resultsmentioning
confidence: 63%
“…Previously, we have shown that NS4B can be expressed in a soluble form using WG‐CFPS and that further reconstitution into liposomes allowed to record quite well‐resolved 13 C‐detected solid‐state NMR spectra . Resolution in spectra using the more sensitive 1 H detection remained however limited . Efficient sample optimization was hampered by the lengthy dialysis step for lipid reconstitution and complete detergent removal .…”
Section: Resultsmentioning
confidence: 99%
“…Cell-free-expressed DHBs Sp articles show ar ather narrow distribution of diameters,c lose to the ones formed in vivo by the human virus HBs S, [33] and their constituent subunits display mainly a-helical secondary structures.T hey show similar antigenic properties as envelopes and SVPs isolated from DHBV-infected ducks.The 2D 1 H-15 NN MR spectra recorded on different preparations served to screen sample quality,a nd spectra from optimized preparations were of asensitivity and resolution that allowed us to initiate structural studies.With the obtained spectra, and by using selective labeling strategies as easily achieved in cellfree reactions,s equential assignments of the protein and subsequent structure determination should become possible, either by using 3D spectroscopy or alternatively by using approaches combining defined selective labeling schemes with 2D spectroscopy. [34] Indeed, as described in the literature, [35] and also shown by us recently on the HCV NS4B protein, [17] virtually clean selective carbon-13 labeling can be achieved in cell-free systems.T hese approaches shall thus open the way to structure investigations of HBs Sf rom the duck and ultimately the human virus,a nd eventually enable us to elucidate the structural features of complex membrane protein assemblies,s uch as these viral surface proteins,t hat are of central importance to infection. Figure 3.…”
Section: Angewandte Chemiementioning
confidence: 61%
“…[10] TheDHBV Sprotein is similar to that of HBV,b ut lacks the cysteine-rich antigenic loop of HBs S, reducing the total size of DHBs Sto167 amino acid residues versus 226 residues for HBs S( see Figure S2 for sequence alignments and Figure 1b for ap redicted model of S). While > 100 kHz MAS NMR spectroscopy, [11][12][13][14][15] cell-free expression, [16][17][18] as well as NMR analyses of large assemblies [19,20] and membrane proteins [21,22] have been demonstrated before,w eh ere show that despite the already high complexity hidden behind every single one of these elements,t heir combination is possible, and allowed us to obtain NMR data of DHBV self-assembled SVPs with suitable resolution and sensitivity.T his method should lead the way for investigations of these,a nd similar, large membrane protein assemblies with currently intractable structures. While > 100 kHz MAS NMR spectroscopy, [11][12][13][14][15] cell-free expression, [16][17][18] as well as NMR analyses of large assemblies [19,20] and membrane proteins [21,22] have been demonstrated before,w eh ere show that despite the already high complexity hidden behind every single one of these elements,t heir combination is possible, and allowed us to obtain NMR data of DHBV self-assembled SVPs with suitable resolution and sensitivity.T his method should lead the way for investigations of these,a nd similar, large membrane protein assemblies with currently intractable structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation